Molecular Characterization of a First-in-Human Clinical Response to Nimesulide in Acute Myeloid Leukemia - Tomaz, Victória; Griesi-Oliveira, Karina; Puga, Renato D.; Conti, Bruno J.; Santos, Fabio P. S.; Hamerschlak, Nelson; Campregher, Paulo V. (Frontiers in Oncology, 2022)
Acute myeloid leukemia (AML) is a hematologic malignancy associated with high morbidity and mortality. Here we describe a case of a patient with AML who presented a partial response after utilization of the non-steroidal anti-inflammatory drug nimesulide. The response was characterized by complete clearance of peripheral blood blasts and an 82% decrease of bone marrow blasts associated with myeloblast differentiation. We have then shown that nimesulide induces in vitro cell death and cell cycle arrest in all AML cell lines (HL-60, THP-1, OCI-AML2, and OCI-AML3). Weighted Correlation Network Analysis (WGCNA) of serial whole-transcriptome data of cell lines treated with nimesulide revealed that the sets of genes upregulated after treatment with nimesulide were enriched for genes associated with autophagy and apoptosis, and on the other hand, the sets of downregulated genes were associated with cell cycle and RNA splicing. Serial transcriptome of bone marrow patient sample confirmed the upregulation of genes associated with autophagy after the response to nimesulide. Lastly, we demonstrated that nimesulide potentiates the cytotoxic in vitro effect of several Food and Drug Administration (FDA)-approved chemotherapy drugs used in AML, including cytarabine.